TINJAUAN YURIDIS PERAN KOMISI PEMBERANTASAN KORUPSI SEBAGAI TRIGGER MECHANISM DALAM PEMBERANTASAN TINDAK PIDANA KORUPSI DI INDONESIA - Yuda, Okta Surya Dharma; Diana, Ledy; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Corruption comes from the Latin "coruptio" or "corrutus", further stated that coruptio it comes from a Latin word corrumpere older. According to European languages such as English, the term corruption is: corruption, corrup. France: corruption. And in Dutch: corruptie. Indonesian in the meaning of the word corruption is decay, depravity, dishonesty, incorruptible, immoral, and deviations from purity. Corruption is a major impact on State finances and the morale of the nation Indonesia in handling must be in accordance with the provisions applicable, which law enforcement must provide a deterrent effect against perpetrators of corruption, so that corruption in Indonesia can be prevented in the sentencing judges should not view feathers, class or race, whoever does corruption laws must be enforced according to the rules and fairness.In Act No. 30 of 2002 said that the Corruption Eradication Commission is to act as a Trigger Mechanism. As the trigger and empowering existing institutions in combating corruption. For effective implementation of this role, the KPK also given the task of enforcement with no need to unplug isntitusi law enforcement agencies such as the police and prosecution. But unlike the Corruption Eradication Commission, the performance of eradication of corruption committed by the Police and the Attorney General can not because it has the maximum number of obstacles.Specifications KPK task is to coordinate and supervise. Especially for the coordination task in fighting corruption can be interpreted that the KPK is the coordinator in the fight against corruption.The weakness of the Commission for this is a limitation of the Human Resources (HR) in preventing and combating corruption, because given the vast territory of Indonesia. The negative impact is going to shrink and eliminate the existence of the role of Police and Prosecutors in combating corruption carried out by the three institutions, including the Corruption Eradication Commission, the Police and the Prosecutor. These three agencies should ideally mutual support and synergy in combating corruption. When this happens, the role of the KPK as an institution triggers and empowering existing institutions in combating corruption (trigger mechanism), is considered not working as it should, because the KPK as an institution coordinator should not be memmonopoli handling of corruption, it is described in Act No. 30 of 2002 on the Corruption Eradication Commission.Key Word : Corruption – Trigger Mechanism – KPK – Human Resources